2016
DOI: 10.5812/ircmj.35788
|View full text |Cite
|
Sign up to set email alerts
|

Family-Based Whole-Exome Sequencing for Identifying Novel Variants in Consanguineous Families with Schizophrenia

Abstract: Background: Schizophrenia (SCZ) is a complex neuropsychiatric disorder characterized by pronounced genetic heterogeneity. Much of the genetic architecture of the disorder has not yet been clearly elucidated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
(36 reference statements)
1
1
0
Order By: Relevance
“…At this juncture identifying such highly penetrant rare variants in functionally relevant gene(s) segregating with the disease phenotype in familial forms of SZ is appealing. We and others in the recent past have used small to medium size families with SZ and reported moderately to highly penetrant rare protein coding variants segregating with disease phenotype (Egawa et al, 2016;Homann et al, 2016;Hornig et al, 2017;John et al, 2018John et al, , 2017Kos et al, 2016;Shirzad et al, 2017;Steinberg et al, 2017;Timms et al, 2013;Zhou et al, 2016) Several genes identified in these studies were broadly connected with glutamatergic pathway and supported the commonly accepted glutamatergic dysfunction hypothesis. These studies reaffirm the highly complex and heterogeneous nature of SZ and at the same time provide evidence for a major/predominant role of glutamatergic pathway genes in SZ etiology based on common and rare variants identified in GWASs and WES respectively.…”
Section: Introductionsupporting
confidence: 62%
“…At this juncture identifying such highly penetrant rare variants in functionally relevant gene(s) segregating with the disease phenotype in familial forms of SZ is appealing. We and others in the recent past have used small to medium size families with SZ and reported moderately to highly penetrant rare protein coding variants segregating with disease phenotype (Egawa et al, 2016;Homann et al, 2016;Hornig et al, 2017;John et al, 2018John et al, , 2017Kos et al, 2016;Shirzad et al, 2017;Steinberg et al, 2017;Timms et al, 2013;Zhou et al, 2016) Several genes identified in these studies were broadly connected with glutamatergic pathway and supported the commonly accepted glutamatergic dysfunction hypothesis. These studies reaffirm the highly complex and heterogeneous nature of SZ and at the same time provide evidence for a major/predominant role of glutamatergic pathway genes in SZ etiology based on common and rare variants identified in GWASs and WES respectively.…”
Section: Introductionsupporting
confidence: 62%
“…More recent whole exome sequencing (WES)/whole genome sequencing in small/modest sized multiplex families have added to the list of inherited rare protein coding variants. These include variants in previously analyzed candidate genes namely RELN (Zhou et al, 2016), UNC13B (Egawa et al, 2016), GRM5, LRP1B, and PPEF2 (Timms et al, 2013),GRIN3B (Hornig et al, 2017), SHANK2 and SMARCA1 (Homann et al, 2016), ANKK1 (Shirzad et al, 2016), RBM12 (Steinberg et al, 2017), TAAR1 (John et al, 2017), TIMP2 (John et al, 2018)and PTPRA (John et al, 2018).These insightful studies suggest the importance of such variants with large/moderate effects in disease development or in increasing the risk in the respective families with disease clustering.…”
Section: Introductionmentioning
confidence: 86%